2018
DOI: 10.3390/su10082793
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Poverty Alleviation Resettlement on Rural Household Livelihood Vulnerability in the Western Mountainous Areas, China

Abstract: Poverty alleviation resettlement (PAR) is China's largest-ever resettlement program and one of China's flagship poverty alleviation initiatives. Resorting to this state-led conversation and development program, the central and provincial governments aim to lift the poor out of the poverty trap and into sustainable livelihoods, by delivering improvements in housing conditions, infrastructure services, public amenities, and living standards. Taking Ankang as an example, this study examines the PAR from the persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 33 publications
3
56
0
2
Order By: Relevance
“…Some argue that the displacement and resettlement of communities should be a last resort [5]; however, China’s central government has relocated millions of households for several reasons, including infrastructure construction (urban demolition, transportation, and hydropower projects). Recent relocation policies have also seen large numbers of people moved to alleviate poverty, address ecological and disaster-related concerns, and make way for major infrastructure construction projects [6,7,8,9]. Many of those being relocated are moving for the first time in their lives away from their rural ancestral homelands and into newly constructed villages, generally located in the same regions [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some argue that the displacement and resettlement of communities should be a last resort [5]; however, China’s central government has relocated millions of households for several reasons, including infrastructure construction (urban demolition, transportation, and hydropower projects). Recent relocation policies have also seen large numbers of people moved to alleviate poverty, address ecological and disaster-related concerns, and make way for major infrastructure construction projects [6,7,8,9]. Many of those being relocated are moving for the first time in their lives away from their rural ancestral homelands and into newly constructed villages, generally located in the same regions [10].…”
Section: Introductionmentioning
confidence: 99%
“…One such policy, the Relocation and Settlement Program of Southern Shaanxi Province (RSP, or Program) cannot be conceptualized as primarily a function of resettlers’ decisions, because it reflects the actions of the state and aims of local governmental development planning [15]. Being different from the project-induced relocation, the RSP aims to achieve sustainable levels of development, restore critical ecosystem services locally, regionally, and globally, alleviate poverty and improve rural households’ livelihood security, enhance social welfare, as well as foster rapid economic growth [7,8,9,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the income gap, poverty and a reduction of demand for labor in rural areas are the driving forces behind immigration. Liu et al [26] found that in terms of PAR in China, there might be livelihood vulnerability arising from the different relocation characteristics. They also suggested that the PAR generally achieves the target of livelihood vulnerability reduction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SNA is a good tool to investigate the network relations and global structure features between individuals within a system. In urban systems, SNA has been applied to measure population migration [40][41][42], urban structure [43], urban construction [44], the urban structure of the ecological relationships [45], and so on.…”
Section: Introductionmentioning
confidence: 99%